(untitled) (Texas Journal of Engineering and Technology, 2023)
Retrofitting existing buildings or increasing the strength of new buildings has become a major issue in the world today to meet the new requirements. Many studies have sought new techniques to renovate old concrete structures. This paper presents four large scale RC box beams with hollow cross-sections measuring 400 mm x 400 mm and 3,000 mm in length that were tested under torsion; two beams were used as a control specimen whereas, the remaining two beams were partially strengthened for torsion on two sides by EBR-CFRP strips. The effeteness of the number of the layer have been discussed. The relationships between torsional moment and twisted angle, and the failure modes of the beam specimens are investigated. The ultimate torque capacity of beam specimens strengthened by EBR has resulted in improvements in the torque capacity of beams. Specifically, the enhancements were 15% when using one layer of CFRP while when using two layers of CFRP was 29%.